Cultural Management Of Character Strengthening In The Post-Pandemic Elementary School Environment - Hijrawatil Aswat; Fitriani B; Nurmin Aminu; Khaerun Nisa Tayibu (CV. Eureka Murakabi Abadi, 2022)
The purpose of this study is to determine various school management patterns in the culture of character education in the post-pandemic elementary school environment. The research method used uses literature studies by looking for relevant theories based on the results of research with cases or problems found, namely character culture management in the elementary school environment with the aim of being a consideration in formulating school activity steps in strengthening character values to students. The results showed several systematic steps in school management including the first, the planning stage in planning an effective character education model. Secondly, the organizing stage aimed at regulating the resources that are in charge or given authority and responsibility to each of their experts in accordance with their respective competencies. Third, the integration stage through curricular, extracurricular, co-curricular, and school culture activities through routine activities or habituation, school climate design, classroom physical environment and the use of digital media. Fourth, the stage of supervision by internal and external parties. Fifth, the evaluation stage by internal parties, evaluation by external parties, then evaluation that produces factors that support and hinder the character education strengthening program, and evaluation that requires follow-up for continuous improvement.